Fechner's legacy in psychology : 150 years of elementary psychophysics - Solomon, Joshua A. (Brill, 2011)
This collection celebrates the 150th anniversary of Fechner's book on Psychophysics (originally published ten years after his epiphany of Oct. 22, 1850). Topics include modern assessments of the problems with which Fechner wrestled. Also included are more general discussions of psychophysical methodology, psychophysical theory, and how these two things can be useful in areas not normally associated with psychophysics. Furthermore, these works provide an entrée into Fechner's ideas, which is perhaps more accessible than his seminal work itself.